ETUDE DE L’EFFET D’HUILE ESSENTIELLE DE LAURIER NOBLE DE L’OUEST ALGÉRIEN SUR SALMONELLA SPP. IN VITRO ET IN VIVO - Karima, Ould Yerou; Boumedienne, Meddah; Aicha, Tir touil (European Scientific Journal, ESJ, 2015)
The foodborne infections have a significant impact on public health. Salmonella is the first bacterial cause, especially because of its general availability in the intestinal tract of poultry, pigs and cattle. This bacteria and essential oil are the subject of study of Laurel essential oil effect of this magic plant Salmonella in vitro and in vivo. In vitro evaluation of the antibacterial activity shows a sensitivity of Salmonella spp. with a Minimum Inhibitory Concentration (MIC) of 2.5 mg.ml-1. In vivo, Wistar rats were infected with Salmonella spp and then treated with the essential oil of Laurel .The microbiological analyese fecal matter from these rats showed that the essential oil of Laurel has a remarkable result on this bacterium pathogen.